Haptic Interaction Science, Engineering and Design (Lecture Notes in Electrical Engineering,, 2018)
This book comprises the proceedings of the second International Conference, AsiaHaptics 2016, held in Kashiwanoha, Japan. The book treats the state of the art of the diverse haptics (touch)-related research, including scientific research of haptics perception and illusion, development of haptics devices, and applications to a wide variety of fields such as education, medicine, telecommunication, navigation, and entertainment. This work helps not only active haptic researchers, but also general readers to understand what is going on in this interdisciplinary area of science and technology.